2015
DOI: 10.5530/pj.2015.3.3
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Sidr Honey on the prevention of ethanol-induced gatroulcerogenesis: role of antioxidant and antiapoptotic mechanism

Abstract: Background: Sider (Ziziphus spina-christi (L.) Desf.) Honey has been used for the treatment of gastrointestinal disorders including peptic ulcer. Aim of the study: The mechanism of the antiulcer effect of sider honey was studied placing emphasis on its role to block oxidative damage and apoptosis during ethanol-induced gastric ulceration in rats. The mechanism of the antiulcer effect of sider honey was studied placing emphasis on its role to block oxidative damage and apoptosis during ethanol-induced gastric u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 34 publications
(26 reference statements)
0
12
0
Order By: Relevance
“…Furthermore, acute toxicity study with date palm extract prior to our project on biological investigation of date extracts revealed extended period of sleep in test animals. All these observations prompted us, as a part of our research on Prophetic medicine (El-Ameen et al 2015; Halabi and Sheikh 2014; Maulidiani et al 2015; Taha et al 2015), to evaluate and compare neuropharmacological effects of two date cultivars growing in Madinah (Ajwah and Safawy) and one growing outside Madinah but within Saudi Arabia (Sukkari).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, acute toxicity study with date palm extract prior to our project on biological investigation of date extracts revealed extended period of sleep in test animals. All these observations prompted us, as a part of our research on Prophetic medicine (El-Ameen et al 2015; Halabi and Sheikh 2014; Maulidiani et al 2015; Taha et al 2015), to evaluate and compare neuropharmacological effects of two date cultivars growing in Madinah (Ajwah and Safawy) and one growing outside Madinah but within Saudi Arabia (Sukkari).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, ethanol improved the free-radical production abilities of the stomach epithelium, and subsequently caused severe stomach epithelial damage [12,48]. Stomach mucus might perform an important role in the epithelial defense in contradiction to ethanol [1,49,50]. The results confirmed that p-Cymene defends the mucosa via concealing extra mucous contrary to extensive gastric destruction.…”
Section: Discussionmentioning
confidence: 68%
“…[38,39] Significances of the present exercise were similar with other amendments quantity gastroprotective and antiulcer achievement gold nanoparticle and herbal composites. [4,40,41] Pre-feeding with the gold nanoparticle, challengingly impassable gastric acid likewise takeover stomach injury in rats forced feeding ethanol, characteristic gastro-protective effect gold nanoparticle easy relatively protection of gastric wall. [42,43] Designated acute inflammation is attracted through ethanol neutrophils penetration the stomach partition.…”
Section: Discussionmentioning
confidence: 99%